Synthesis and Characterization of Photocatalytic Performance of Rutile-Tio2 Nanorod Arrays for Solar Hydrogen Generation - Qasim, Amin K.; Jamil, Lazgin A.; Chen, Qiao (Science Journal of University of Zakho, 2017)
Single crystalline rutile TiO2 nanorods (TNRs) films have been grown on the fluorine doped tin oxide (FTO) substrates using a one pot hydrothermal method, have attracted great attention because of favorable applications in the  photoelectrochemical water splitting system. The effect of the reaction conditions on the morphology, crystal orientation and photocatalytic activity has been systematically investigated. The X-ray diffraction (XRD) pattern shows that two diffraction peaks at 36.3° and 63.2° correspond to the (101) and (002) planes of the tetragonal rutile TiO2 nanorod, respectively. The scanning electron microscope (SEM) of the samples indicates that the TiO2 array surface morphology and orientation are highly dependent on the reaction parameters, such as temperature, reaction time and the titanium precursor concentration. In a typical condition of the hydrothermal method at 0.3ml of TBO and 160°C for 3 hr, a small diameter and short length 190 nm and 2.2 µm of TiO2 nanorods respectively, are grown on florien doped tin oxide (FTO) substrate. When synthesized TiO2 nanorods photocatalyst was irradiated under illumination of simulated AM 1.5G solar light (100 mW cm−2) achieves an overall Photocurrent density of 1.80 mA/cm2 with a maximum photoconversion efficiency of ~1.6%. The results suggest that these dense and aligned one-dimensional TiO2 nanorods are promising for hydrogen generation from water splitting based on PEC cells.
Keywords: Photocatalytic; Rutial-TiO2 Nanorod; Solar Hydrogen Generation; Hydrothermal Synthesis